Extended Therapy With Pegylated Interferon and Weight-Based Ribavirin for HCV-HIV Coinfected Patients - Chung, Raymond T. (2012)
BACKGROUND: It is unknown whether extended treatment with pegylated interferon (PEG) and weight-based ribavirin (WBR) results in higher rates of sustained virologic response (SVR) among HCV-HIV coinfected patients compared with standard duration therapy. OBJECTIVE: The study aimed to measure rates of SVR among coinfected patients who received extended therapy with PEG plus WBR. METHODS: HCV-HIV coinfected subjects were treated with PEG and WBR, and those who achieved early virologic response (EVR; ≥2 log decrease in HCV RNA from baseline or HCV RNA<600 IU/mL) at week 12 were eligible to continue treatment for 72 weeks. SVR (HCV RNA<60 IU/mL) was measured 24 weeks after treatment discontinuation. Predictors of SVR were assessed in simple and multivariate logistic regression. RESULTS: A total of 329 subjects enrolled at 36 sites. Of 184 subjects who achieved EVR, 169 entered Step 3: 89% male, 52% White, 29% Black, and 71% HCV treatment naïve. The overall SVR rate was 27% (95% CI, 22%–32%) among all subjects, and 33% (95% CI, 27%–40%) among the 223 who were HCV treatment naïve. In exploratory analyses, among 120 treatment-naïve subjects who entered Step 3, the SVR rate was 62% (95% CI, 52%–70%). In this subgroup, predictors of SVR were HCV genotype 2 or 3 (P = .03), HCV RNA <800,000 IU/mL at study entry (P = .05), and achievement of complete EVR (HCV RNA<600 IU/mL at week 12; P < .0001). CONCLUSION: Among all subjects, we observed a comparable overall SVR rate to prior studies of subjects treated for 48 weeks. Extended treatment with PEG and WBR may be beneficial to subsets of coinfected patients, specifically those who are treatment naïve and achieve complete EVR.